Analisis pengaruh pendapatan perkapita dan belanja modal terhadap tingkat kemiskinan di Pulau Sumatera - Wenny Tri Septiani; Zamzami Zamzami; Candra Mustika (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2019)
This study aims to: 1) To analyze and determine the development of per capita income, capital expenditure, and poverty levels on the island of Sumatra. 2) To analyze and determine the effect of per capita income and capital expenditure on poverty levels in Sumatra Island. The research analysis tool used panel data regression analysis tools. Based on the results of panel data regression, it can be concluded that per capita income and capital expenditure on the poverty level together have a significant effect. Whereas partially only the per capita income variable had a significant and negative effect on the poverty level, while capital expenditure had no significant and positive effect on the poverty level. Keywords: Poverty rate, Per capita income, Capital expenditures